2022
DOI: 10.1038/s41467-022-30121-0
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and macrocyclization-induced emission enhancement of benzothiadiazole-based macrocycle

Abstract: We presented an effective and universal strategy for the improvement of luminophore’s solid-state emission, i.e., macrocyclization-induced emission enhancement (MIEE), by linking luminophores through C(sp3) bridges to give a macrocycle. Benzothiadiazole-based macrocycle (BT-LC) has been synthesized by a one-step condensation of the monomer 4,7-bis(2,4-dimethoxyphenyl)−2,1,3-benzothiadiazole (BT-M) with paraformaldehyde, catalyzed by Lewis acid. In comparison with the monomer, macrocycle BT-LC produces much mor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 61 publications
0
16
0
Order By: Relevance
“…AIE luminogens (AIEgens) that are brightly emissive in the aggregated state, known as the opposite of aggregation-caused quenching effect, generally possess adequate conformational freedom that can dissipate excited state energy in a nonradiative decay manner . Ideally, the RIM mechanism plays a significant role in triggering AIE. Inspired by the unique AIE-active behaviors of pillararenes, , we investigated the fluorescence properties of P5-2CN in the THF/water mixture by recording their PL spectra with different water fractions ( f w ). The TSCT band at 520 nm remained nearly unchanged when the f w increased from 0 to 50%.…”
Section: Resultsmentioning
confidence: 99%
“…AIE luminogens (AIEgens) that are brightly emissive in the aggregated state, known as the opposite of aggregation-caused quenching effect, generally possess adequate conformational freedom that can dissipate excited state energy in a nonradiative decay manner . Ideally, the RIM mechanism plays a significant role in triggering AIE. Inspired by the unique AIE-active behaviors of pillararenes, , we investigated the fluorescence properties of P5-2CN in the THF/water mixture by recording their PL spectra with different water fractions ( f w ). The TSCT band at 520 nm remained nearly unchanged when the f w increased from 0 to 50%.…”
Section: Resultsmentioning
confidence: 99%
“…This is attributed to the spatial separation and the suppression of non-radiation relaxation caused by the macrocyclic topological structure. 11 The fluorescence quantum yields in solution were also tested. In chloroform, the macrocycle ( Φ PL = 12.6%) exhibits higher quantum yields than the monomer ( Φ PL = 7.1%), which is consistent with solid-state luminescence.…”
Section: Resultsmentioning
confidence: 99%
“…Herein, we designed and synthesized pyridine/pyridinium-based macrocycles PC and PC 2+ , using our synthetic method for functional biphen[ n ]arenes. 49,50 All these macrocycles exhibited prolonged phosphorescence lifetime and improved quantum efficiencies in comparison with their monomers, thus exhibiting macrocyclization-induced phosphorescence enhancement (MIPE). Single crystal X-ray diffraction analysis and photophysical characterization revealed that this enormous enhancement is because of the restriction of the macrocyclic skeleton for the phosphorescent units which efficiently suppressed the radiative decay of the singlet state and triplet state, and nonradiative decay of the triplet state.…”
Section: Introductionmentioning
confidence: 99%